Empowering environmental awareness in Kindergarten: A community development initiative on plastic waste management - Aiko, Keisya Putri; Nurmalasari, Siti; Reza, Muhammad; Nadhifa, El Pasya Athalla; Lumi, Amiko Nashita; Purwanto, Edi (Penamas: Journal of Community Service, 2024)
This study documents a community development initiative at Ar-Rasyid Kindergarten to educate young students about plastic waste management through practical activities. The method involved conducting training sessions or workshops and providing guidance in making pencils from plastic waste. Guided by a community service team, kindergarten students engaged in hands-on projects to repurpose plastic bottles into pencil holders. Pre-tests assessed initial understanding, revealing varying levels of awareness among students. Following educational sessions and post-tests, significant improvements were observed in students' comprehension of recycling and environmental stewardship. The initiative fostered creativity and practical skills and instilled a sense of environmental responsibility in students. This underscores the importance of early education in shaping sustainable behaviors and promoting a cleaner, healthier environment. Such initiatives highlight the potential of educational interventions to empower future generations in combating plastic pollution and fostering sustainable practices.